A novel flower-like hierarchical aluminum-based MOF anode for high-performance lithium-ion batteries. Issue 39 (23rd September 2022) - Tong, Yihong; Xu, Hongyuan; Li, Ting; Kong, Zhao; Li, Jiawei; Fan, Qi Hua; Xu, Hui; Jin, Hong; Wang, Keliang
Abstract : Metal–organic frameworks, an emerging electrode material, are mostly synthesized by using costly, limited reserve and environmentally unfriendly metals as nodes. Abstract : Metal–organic frameworks, an emerging electrode material, are mostly synthesized by using costly, limited reserve and environmentally unfriendly metals as nodes. In this work, a novel Al-based MOF was designed using cheap Al 3+ as the active site and green citric acid as the organic ligand in a facile and environmentally friendly way. PVP was introduced to tune the stacking arrangement of the MOF nanosheets, delivering a flower-like hierarchical structural MOF. This unique structure with robust three-dimensional porous channels can effectively relieve stress and increase the contact area with the electrolyte, thereby improving the structural stability of the electrode during cycling and increasing the Li-ion diffusion rate. Upon testing, the pure MOF anode maintains a high capacity of 1103.9 mA h g −1 after 350 cycles at 0.1 A g −1, which is 255% of the initial discharge capacity. Moreover, it maintains impressive capacities of 995, 962, 799, and 610 mA h g −1 after 500 cycles at 0.5, 1, 2 and 5 A g −1, respectively. This work would be a great inspiration for the development of pristine Al-based MOFs as a potential anode material for high-performance LIBs.